2018
DOI: 10.1037/pap0000196
|View full text |Cite
|
Sign up to set email alerts
|

Parental trauma and adult sibling relationships in Holocaust-survivor families.

Abstract: Evidence suggesting accentuated sibling differentiation and de-identification is observed among adult children of Holocaust survivors, manifested in the respective family roles of each sibling, their relationships vis a vis the parents, and also in the siblings’ general adaptation styles. These dissimilarities are often accompanied by a negative quality of the sibling relationships. It is proposed that (dissociated) affects and enactments of unsynthesized parental trauma infuse implicit and explicit interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 103 publications
0
10
0
Order By: Relevance
“…Research on OHS has led to the recognition that the effects of parental trauma on children in the family are complex and multidetermined. Children’s differential susceptibilities, and the interactions among multiple factors, can have varied developmental outcomes leading to differences among OHS, even within the same family (Danieli et al, 2016; Felsen, 2018; Kellermann, 2009).…”
Section: Previous Research On Offspring Of Holocaust Survivorsmentioning
confidence: 99%
“…Research on OHS has led to the recognition that the effects of parental trauma on children in the family are complex and multidetermined. Children’s differential susceptibilities, and the interactions among multiple factors, can have varied developmental outcomes leading to differences among OHS, even within the same family (Danieli et al, 2016; Felsen, 2018; Kellermann, 2009).…”
Section: Previous Research On Offspring Of Holocaust Survivorsmentioning
confidence: 99%
“…I wanted to know why and how this ancestral ancient history was still present in my body even when disconnected from my family. The research showed me how TGT could show up as an avoidant attachment, a sense of rootlessness, or lack of place attachment (Braga et al, 2012;Felsen, 2018). Early research already pointed to the fact that ancestral legacy could affect one's attachment styles, which could also be seen as TGT (Bar-On et al, 1998;Felsen, 2018;Wallin, 2007).…”
Section: An Equanimous Collective Traumamentioning
confidence: 99%
“…The research showed me how TGT could show up as an avoidant attachment, a sense of rootlessness, or lack of place attachment (Braga et al, 2012;Felsen, 2018). Early research already pointed to the fact that ancestral legacy could affect one's attachment styles, which could also be seen as TGT (Bar-On et al, 1998;Felsen, 2018;Wallin, 2007). Nothing began with me, but in the history of who came before me (Wolynn, 2017).…”
Section: An Equanimous Collective Traumamentioning
confidence: 99%
“…The presence of life-and-death themes in the family atmosphere lends an absolutism to the negative judgments that siblings might feel toward each other, because they feel that the sibling "is killing the parents," who have suffered already so much in previous times and should be protected from any further pain (Felsen, 2018). Such intensely negative feelings often resulted in complete cutoff in relationships among adult siblings after the death of the survivor parents.…”
Section: Adult Sibling Relationships In Holocaust Families: Resentmen...mentioning
confidence: 99%
“…The relationships among siblings in many Holocaust families are suffused with mutual resentments, often resulting in total cutoff after the parents are deceased. Although sibling differentiation is a natural process that takes place in all families, I propose that normative processes of deidentification are polarized and intensified by the presence of trauma-related dynamics in the family (Felsen, 2018). Empirical findings reflect that the focus on parental needs and the imperative to protect them is a common and overarching concern for many children of survivors.…”
Section: Covid-19: Conversations With Ohsmentioning
confidence: 99%